Precise ro-vibrational analysis of molecular bands forbidden in absorption: The ν8+ν10 band of the 12C2H4 molecule - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Kashirina N. V. Nadezhda Vladimirovna; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann; Horneman V.-M. (2015, 2015)
Title screen